2023
DOI: 10.3390/su15021710
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Movement Patterns and the Effects of Spatial Configuration in a Cultural Heritage and Urban Destination: The Case of Madaba, Jordan

Abstract: This study investigated the impact of spatial configuration on tourist movement patterns and its role in managing cultural heritage destinations in the city of Madaba. Understanding tourist movement patterns is important for the development of sustainable tourism practices in cultural heritage destinations, as it can help to identify attractions of high tourist impact and inform the development of strategies to mitigate the negative impacts on site preservation and management. Madaba is one of the largest home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For several feature vectors such as users' candidate and current access POIs, Zhang et al (2020) then designed a feature fusion model based on multilayer neural network to improve the accuracy of POI access prediction. Jamhawi et al (2023) found that attraction points, routes, physical and visual connectivity, accessibility, and the location of tourist activity arrangements are all influential to the spatial behavior of tourists.…”
Section: Related Workmentioning
confidence: 99%
“…For several feature vectors such as users' candidate and current access POIs, Zhang et al (2020) then designed a feature fusion model based on multilayer neural network to improve the accuracy of POI access prediction. Jamhawi et al (2023) found that attraction points, routes, physical and visual connectivity, accessibility, and the location of tourist activity arrangements are all influential to the spatial behavior of tourists.…”
Section: Related Workmentioning
confidence: 99%
“…Khaled [34] conducted a space syntax visibility analysis of roads in historic districts and used an agent to model two different historic districts in the north of Lebanon to establish a research framework to find the critical factors affecting tourists' wayfinding patterns. Jamhawi [35] investigated the effects of spatial configurations on tourist flow patterns and the impacts on cultural heritage sacred sites. The main focus in the study of the relationship between scenic spots and external road network connectivity is to study the distribution of popular scenic spots and the factors affecting them, as well as the impacts of the locations of the scenic spots and road facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding social and cultural effects, the tourism industry plays a significant role in cultural preservation and heritage management within a region. It profoundly influences changes in local customs, values, and traditions [ 18 ]. In terms of environmental effects, relevant research focuses on exploring the balance between attraction development and protection, mainly involving the environmental impact of tourist attractions on the surrounding areas, such as the sustainable development of natural resources, environmental pollution, and carbon footprint [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%